Does undergraduate student research make a difference in postgraduate professional life? [Mezuniyet öncesi araştırma deneyimi mezuniyet sonrasında bir fark yaratıyor mu?] - (:unkn) unknown (Marmara University, 2011)
Objective: To compare medical graduates with and without undergraduate research experience in relation to oral or poster presentations after graduation. Materials and Methods: Graduates of Marmara Medical School were enrolled in this cross-sectional study between 20th February and 19th May 2009. Students graduating in 2005 and 2006 were classified as student research exposed and those graduating in 2001 and 2002 were classified as student research naive groups. Two different questionnaires were prepared for the groups and analysed electronically. All graduates of the mentioned years were contacted by telephone (n=425). The reply rates for the questionnaires were 45% in the exposed and 25.5% in the naive groups. Results: Fifty one point six percent of the participants were female and 25.5% were residents. 90.1% of the exposed group were satisfied with their research experience and agreed that this experience had a positive influence on their professional life. There was no statistically significant difference between the study groups for oral or poster presentations during the first 2 years after graduation. Research experience was found to be useful for preparing questionnaires, defining research aims and collecting data. Conclusion: The satisfaction rate from the research experience and the motivation for new research were high in the exposed group. However, an added value of the research experience could not be shown quantitatively.
Keywords: Research activities; Research education; Undergraduate medical education